The influence of loads of various magnitudes and directions on the visual acuity of high-qualified visually impaired sprinters - Лейля Аджаметова; Людмила Шестерова (Слобожанський науково-спортивний вісник, 2023)
Purpose: determine the impact of loads of different magnitudes and directions on the visual acuity of a highly qualified female athlete with visual impairments, specializing in sprinting.